Advanced dynamics : rigid body, multibody, and aerospace applications - Jazar, Reza N. (Hoboken, N.J. : Wiley, 2011)
"According to the author and reviewers, more than 50% of the material taught in courses such as Advanced Dynamics, Mutibody Dynamics, and Spacecraft Dynamics is common to one another. Where graduate students in Mechanical and Aerospace Engineering may have the potential to work on projects that are related to any of the engineering disciplines, they have not been exposed to enough applications in both areas for them to use this information in the real world. This book bridges the gap between rigid body, multibody, and spacecraft dynamics for graduate students and specialists in mechanical and aerospace engineering. The engineers and graduate students who read this book will be able to apply their knowledge to a wide range of applications across different engineering disciplines. The book begins with a review on coordinate systems and particle dynamics which will teach coordinate frames. The transformation and rotation theory along with the differentiation theory in different coordinate frames will provides the required background to learn the rigid body dynamics based on Newton-Euler principles. Applications to this coverage can be found in vehicle dynamics, spacecraft dynamics, aircraft dynamics, robot dynamics, and multibody dynamics, each in a chapter. The Newton equations of motion will be transformed to Lagrange equation as a bridge to analytical dynamics. The methods of Lagrange and Hamilton will be applied on rigid body dynamics. Finally through the coverage of special applications this text provides understanding of advanced systems without restricting itself to a particular discipline. The author will provide a detailed solutions manual and powerpoint slides as ancillaries to this book"--
Frontmatter -- Fundamentals. Part Introduction -- Fundamentals of Kinematics -- Fundamentals of Dynamics -- Geometric Kinematics. Part Introduction -- Coordinate Systems -- Rotation Kinematics -- Orientation Kinematics -- Motion Kinematics -- Multibody Kinematics -- Derivative Kinematics. Part Introduction -- Velocity Kinematics -- Acceleration Kinematics -- Constraints -- Dynamics. Part Introduction -- Rigid Body and Mass Moment -- Rigid-Body Dynamics -- Lagrange Dynamics -- References -- A: Global Frame Triple Rotation -- B: Local Frame Triple Rotation -- C: Principal Central Screw Triple Combination -- D: Industrial Link DH Matrices -- E: Trigonometric Formula -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Dynamics; TECHNOLOGY & ENGINEERING -- Material Science; Dynamics; Electronic books; Electronic books